PÉDAGOGIE UNIVERSITAIRE RÉNOVÉE À L’ÉPOQUE DE LA PANDÉMIE : COMMENT PASSER DE L’AUTRE CÔTÉ DE L’ÉCRAN ? - Sujecka-Zając, Jolanta (Neofilolog, 2021)
The 2020/2021 pandemic year has been difficult for teachers at all levels of education including higher education. There was a need to switch quickly to another type of education that would achieve the same objectives as before. How did the university teachers face this challenge? What consequences have been drawn for university teaching in general? We propose to take a global perspective of the state of current university pedagogy to highlight the need to renovate its approaches and to put the learner at the center of the process so to provide pedagogical support in his learning. We will analyze the results of three surveys concerning remote teaching and learning in Poland and in Europe. Finally, we will show what tools can be used to better monitor students` learning in virtual classes.